Pengaruh Keterlibatan Kerja dan Orientasi Belajar terhadap Kinerja Karyawan dengan Mediasi Kompetensi - Aria Elshifa; Ary Dwi Anjarini; Aghus Jamaludin Kharis; Aria Mulyapradana (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
Abstract The purpose of this study was to examine and analyze the effect of work engagement and learning orientation on competence. To test and analyze the effect of work engagement, learning orientation and competence on employee performance. To test and analyze the effect of work engagement and learning orientation on employee performance mediated by competence.The population in this study were employees of PT. Adira Dinamika Multi Finance Tbk. The Pekalongan Branch is 65 Debt Collector employees. The research method uses analytical tools in the form of mediation test analysis.The results of the study were obtained as follows. Work involvement and learning orientation have a positive and significant influence on employee competencies in PT. Adira Dinamika Multi Finance Tbk. Pekalongan Branch. Work involvement, learning orientation and competence have a positive and significant impact on employee performance of PT. Adira Dinamika Multi Finance Tbk. Pekalongan Branch. Competence as a variable mediating the effect of work involvement and learning orientation on employee performance of PT. Adira Dinamika Multi Finance Tbk. Pekalongan Branch.